Impact of baseline impaired sleep, depressive symptoms and pain on physical activity in the FINGER multidomain lifestyle trial: Prevention (nonpharmacological) / Exercise. (7th December 2020) - Pietilä, Eija Kristiina; Hall, Anette; Ngandu, Tiia; Kivipelto, Miia; Antikainen, Riitta; Havulinna, Satu; Kulmala, Jenni; Laatikainen, Tiina; Levälahti, Esko; Paajanen, Teemu; Soininen, Hilkka; Strandberg, Timo; et al.
Abstract: Background: Physical inactivity is a major concern for public health. Physical activity (PA) is an important protective factor against Alzheimer's disease and dementia. Therefore, possible barriers to PA, such as impaired sleep, depressive symptoms and pain may need to be considered in prevention programs. The study aim was to investigate whether impaired sleep, depressive symptoms and pain at baseline would impact PA after a 2‐year multidomain lifestyle intervention in individuals at‐risk of dementia. Method: The data was from the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) 2‐year randomized controlled trial in 1260 older individuals at‐risk of dementia. PA (active/inactive), sleep duration (hours/night), and sleep quality (composite index based on 6 questions) were self‐reported. Depressive symptoms were assessed using the Zung scale, and bodily pain using RAND‐36. Associations of impaired sleep, depressive symptoms, or pain at baseline with PA at baseline and at the 2‐year visit were assessed using binary logistic regression models, adjusted for randomization group, age, sex, education, marital status, and body mass index. Result: At baseline, participants sleeping on average ≤6 hours per night (n=268, 21%) reported poorer sleep quality, more depressive symptoms, more pain, and were also less physically active than participants with longer sleep duration. Participants with more depressive symptoms were less likely to be physically active at baseline (OR=0.97, 95%CI 0.95‐0.99). The odds of being physically active at 2‐year visit were increased in the intervention group, compared to control group (OR=1.9, 95%CI 1.4‐2.7). Being physically active at baseline also increased the odds of being physically active at 2‐year visit, (OR=8.4, 95%CI 5.8‐11.2). Compared to normal sleep duration (between >6 and <9 hours per night) at baseline, short sleep duration (≤6 hours per night) reduced the odds of being physically active at the 2‐year visit (OR=0.5, 95%CI 0.4‐0.8). Conclusion: These preliminary findings from FINGER trial suggest that especially impaired sleep may need to be considered in prevention programs. Due to the associations between sleep quality, sleep duration, depressive symptoms and pain, further investigation is highly needed.